Development of lymphocyte specific internalising aptamers - Millroy, Laura Ann (My University, 2014)
Aptamers are synthetic nucleic acid molecules designed to bind with high specificity and affinity to a selected target. The aptamer selection method, called the systematic evolution of ligands by exponential enrichment (SELEX), was first described in 1990 and has been adapted for the selection of aptamers for a number of applications. One such application is the selective targeting of cells for therapeutic delivery. This thesis explores this application with the selection and characterisation of internalising aptamers specific to the T lymphocyte specific receptor, CD7. The CD7 receptor is expressed on thymus derived progenitor lymphocytes and remains after T cell activation and expression of the CD4 receptor. As such, the CD7 receptor is a noteworthy target for lymphocyte cancers, HIV-1 and other T lymphocyte tropic viruses. A heterogeneous pool of internalising CD7-aptamers was enriched through six rounds of positive selection in a stably transduced CD7-HeLa cell line. Aptamers were selected using a modified whole cell SELEX method that selected specifically for internalising aptamers. Aptamer specificity for CD7-HeLa cells over HeLa cells was screened by flow cytometry. CD7 specific aptamers were screened for binding after blocking CD7-HeLa cells with an anti-CD7 antibody. Eight CD7 specific aptamer clones were selected from CD7-HeLa screening for evaluation in Jurkat cells (T lymphocyte cell line endogenously expressing the CD7 receptor). Three aptamer clones showed high level binding to Jurkat cells by flow cytometry (CSIR 3.14, CSIR 3.37 and CSIR 3.42). Kinetic analysis of aptamer internalisation was analysed using flow cytometry and determined to be within the femtomolar range. Aptamer CSIR 3.14 had a dissociation constant of 2.1 fM and an association rate of 4.7 ± 2.4 × 105 Molar-1minute-1, aptamer CSIR 3.37 had a dissociation constant of 0.23 fM and an association rate of 4.3 ± 3.3 × 106 Molar-1minute-1 and aptamer CSIR 3.42 had a dissociation constant of 1.1 fM with an association rate of 7.9 ± 5.1 × 105 Molar-1minute-1. Aptamer CSIR 3.14 internalisation was tracked by confocal microscopy and the kinetics calculated with an association rate of 6.3 × 104 Molar-1minute-1 and Kd of 13 fM. Deletions within the CSIR 3.14 sequence that altered the predicted structures significantly reduced the aptamer binding. Combined, the data presented in this thesis identifies aptamer CSIR 3.14 as a lymphocyte specific internalising aptamer with potential for therapeutic delivery.
Keywords: Ligands (Biochemistry); Nucleic acids; Chemical kinetics